Efektifitas Loading Cairan Koloid Terhadap Kejadian Hipotensi Pada Pasien Sectio Caesarea Dengan Spinal Anestesi Di RSD Dr A.Dadi Tjokrodipo Bandar Lampung - Mustika Sari; Galih Pria Pambayun; Ambar Samekto (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
RSD Dr.A. Dadi Tjokrodipo Bandar Lampung, sectio caesaria patients in the last 3 months of 2021 totaled 40 patients. Hypotension or decrease in Mean Arterial Pressure (MAP) in caesarean section often occur consequence spinal anesthesia due to overall blockade effect on the sympathetic nervous system . Study this aim for This study aims to determine the effect of loading colloid fluid in sectio caesarea patients with spinal anesthesia. Method study qualitative with a descriptive research design is a research that tends to use analysis . Population study 40 patients sectio caesarea with spinal anesthesia at Dr A. Dadi Tjokrodipo Hospital Bandar Lampung with amount sample of 8 patients. From result study "Effectiveness of Loading Colloidal Fluids Against Hypotension in Sectio Caesarea Patients With Spinal Anesthesia at Dr A. Dadi Tjokrodipo Hospital Bandar Lampung" could obtained results that Patient Sectio Caesarea performed Partial spinal anesthesia big experience hypotension (87.5%) due to effect of spinal anesthesia , so that required gift fluid colloid for raise pressure blood . Effect gift fluid colloid on patient cesarean section hypotension really mean for normalize return pressure blood patients (75%). Based on results Paired Samples T-Test statistical test obtained value of Sig.(2-tailed) = 0.001 or < 0.05 which means there is significant difference on the Mean Arterial Pressure (MAP) before and after gift fluid colloid on patient sectio caesarea with spinal anesthesia at Dr A. Dadi Tjokrodipo Hospital, Bandar Lampung